Stock Market Integration of India with Rest of the World : An Empirical Study - Bhattacharjee, Sudarshan; Swaminathan, A. M. (Indian Journal of Finance, 2016)
The present study conducted an analysis of the stock market integration of India and a few selected countries of the globe. The study used the Engle-Granger bivariate co-integration test for the analytical purpose of ascertaining the long run equilibrium relation among the countries. The long run relationship of India with some of the selected countries across the globe was analyzed over three different phases. It was observed that cointegration of India with other stock markets was increasingly improving over the years with financial liberalization. The study found that the Indian stock market was more responsive to the other Asian stock markets during the recession phase than in any other sub-sample periods.